Physiological responses of unilateral versus bilateral acute resistance training among trained women / Nur Khairunisa Abu Talip - Abu Talip, Nur Khairunisa (2015)
Resistance training (RT) refers to a method of physical conditioning of complex programming which consists of progressive and various training techniques to achieve the desired training goals. An appropriate programme design is the key to success; where exercise selection is one of the critical factors. The selection of exercise will expose different stimulation as in the application of the specific adaptation on imposed demand principle. The option of choosing either bilateral (BI) or unilateral (UNI) exercise is an important decision to perform in the construction of any strength or RT programme. This study aimed to investigate the physiological responses of unilateral versus bilateral acute RT on heart rate (HR), blood pressure (BP), blood lactate (BLa), blood glucose (BG), creatine kinase (CK) and rate of perceived exertion (RPE). Sixteen (n = 16) trained women with mean age of 23.31 (SD = 1.35) years old went through a total body exercise session for each unilateral and bilateral protocols which both consisted of major muscles group for 80% 1RM, 10 repetitions to maximal effort for 3 sets. The results revealed that all variables examined including HR, systolic blood pressure (SBP), diastolic blood pressure (DBP), BLa, BG, CK and RPE were statistically changed (p < .001) across the times.Apart from that, unilateral and bilateral RT imposed significantly different stimulus on SBP, BLa and CK (p < .05).